Environmental health practitioners potentially play a key role in helping communities adapt to climate change - Busisiwe Shezi; Angela Mathee; Wellington Siziba; Renée A. Street; Nisha Naicker; Zamantimande Kunene; Caradee Y. Wright (BMC, 2019)
Abstract Background Vulnerable population groups in South Africa, especially those living in poverty, young children, women, the elderly and people with pre-existing diseases, are susceptible to new or exacerbated health threats resulting from climate change. Environmental Health Practitioners (EHPs) can play an important role in helping communities adapt to climate change health impacts, however, effective coordination of this requires further understanding of their roles in implementing climate change-related adaptation actions in communities. Methods A cross-sectional survey using convenience sampling was undertaken at the January 2017 conference for EHPs hosted by the South African Institute of Environmental Health in Cape Town. All EHPs who attended the conference were invited to complete a study questionnaire that requested information on participant demographics, as well as climate change related-knowledge, practices and perceptions. Results Majority of participating EHPs (n = 48; 72.8%) had received formal or informal training on climate change and health. Thirty-nine percent of EHPs indicated that they had a climate change and health-related committee / working group in their department, a policy or strategy (41.0%) and budget allocated for climate change and health-related work (51.5%). A total of 33.3% had participated in climate change-related projects. Majority (62.2%) of EHPs believed that they should play a supportive role in addressing climate change while 37.8% believed that EHPs should play a leading role. Conclusions Recognising the need for raising awareness about climate change adaptation as well as implementing appropriate interventions to combat climate-related ill health effects, especially among vulnerable groups, EHPs are well-placed to adopt significant roles in helping communities to adapt to climate change.